Pengaruh Kualitas Pelayanan Event Meeting Terhadap Kepuasan Pelanggan di Phenom Event Indonesia - Alantoni, I Nyoman; Ariasri, Ni Nyoman Reni; Swandewi, Ni Kadek (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
This research method uses quantitative methods. The statistical tools used in this study used the normality test, multicollinearity test, heteroscedasticity test, determination test, and t test. The sample used in this study was 17 respondents, namely repeater client Phenom Event Indonesia in the 2018-2022 period. The data collection techniques used were surveys, interviews, and documentation studies. Based on the results of the t test, it is known that the t-count value is 8.390. This value is greater than the t-table value (1.746). This shows that service quality affects customer satisfaction. Based on the test of the coefficient of determination found a value of 82.4%. This value indicates the variable service quality contributes 82.4% to customer satisfaction. while the remaining 17.6% is influenced by other variables not discussed in this study.